My Precious Life: Strategi Membabat Narasi Mitos Pulung Gantung sebagai Rekonstruksi Perilaku Sosial Kelompok Rentan Bersama PKK Dusun Ngampel Gunungkidul: indonesia - Asfia, Nur; Putra, Dimas Brian Adi; Gunawan, Alvin Nuru Syah; Hidayat, Raka Pramudita; Paramesti, Mahia Nasywa; Kushartati, Sri (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Data from the Yogyakarta Regional Police indicate that Gunungkidul Regency has the highest suicide rate in Yogyakarta. In Gunungkidul, nearly 20 cases happen every year. The cases of suicide in Gunungkidul are usually linked with the myth of "pulung gantung." As a matter of fact, existing studies reveal that the prevalent cause of suicide in Gunungkidul is depression. Considering the condition above, the PKM-PM UAD team came up with the "My Precious Life" program, consisting of a series of activities: Training of Trainers, Mbalang Lintang Game, and Psychological Campaign. The implementation methodology will consist of a series of trainings involving active participation from the local community. The "My Precious Life" program gained support from village governments, village, and hamlet PKK cadres, and health institutions for its execution to ensure maximum involvement and a significant impact on the results. Results of this program indicate that there is a significant increase in knowledge and skills for the early detection community and a decrease in elderly individuals with depressive tendencies after playing mbalang lintang. Moreover, this has created closer ties between residents and the rest of the supporting institutions involved, which in turn have given rise to many new initiatives that will help continue this program well into the future. The conclusion from this activity was that for achieving the community service goals, collaboration and active participation from all parties involved were very important. This is a very useful program to the community, which can act as a role model that may help similar activities elsewhere